Analisis Efektivitas Nanocurcumin Terhadap Ekspresi TNF-α Dan Diameter Lesi Pada Mencit (Mus musculus) Yang Diinduksi Endometriosis - Dharma, Komang Ayu Vanessa; Pribadi , Florence; Kusumah , Irwin Priyatna (Journal of Pharmaceutical and Sciences, 2026)
Endometriosis is a chronic gynecological disease characterized by the growth of endometrial-like tissue outside the uterus, which triggers local inflammation and lesion progression. The pathological process involves increased proinflammatory cytokines, including TNF-α, and activation of proliferative and angiogenic pathways. Nanocurcumin, with higher bioavailability compared to conventional curcumin, is known to have the potential to modulate inflammation and inhibit ectopic tissue growth. This study aimed to analyze the effect of nanocurcumin at a dose of 10 mg/kgBW on TNF-α expression and endometriosis lesion diameter in endometriosis-induced mice. The laboratory experimental study used a post-test only control group design with three treatment groups (control, nanocurcumin after induction, and nanocurcumin before induction), each consisting of 10 mice. TNF-α expression was measured using the ELISA method, while lesion diameter was assessed macroscopically. Data analysis was performed using the Shapiro–Wilk normality test, Levene's homogeneity test, ANOVA, and Tukey's extended test. The results showed no significant difference in TNF-α levels between groups (p = 0.933). However, there was a significant difference in endometriosis lesion diameter (p < 0.001), with the nanocurcumin group showing the greatest lesion shrinkage compared to the control and other treatment groups. Nanocurcumin significantly reduced the diameter of endometriosis lesions in mice, although it did not significantly reduce serum TNF-α levels. These findings suggest that the therapeutic effects of nanocurcumin may be mediated through local mechanisms that are not fully reflected in serum biomarkers.